(untitled) (PerCursos, 2021)
The adaptation of climate change phenomenon is an issue of great importance in the actual context of public policies for urban planning. When it comes to sites of cultural-historical value and cultural heritage assets, the effect of climate change can pose a major challenge to ensuring their conservation. Thus, the present paper aims to present a narrative literature review of scientific articles and reference bibliography about the impact of climate change on heritage, critically comparing the Brazilian case with the international context, especially the European one. It was stipulated as the temporal delimitation of the last two decades, between 2000 and 2020, five years after the first global climate conference of the UN (United Nations), with the consolidation of the climate commitment and the expansion of signatory countries. The applied methodology is the bibliographic review and compilation of the data obtained from the publications, making use of the critical-comparative analysis. As a result, it is expected to contribute to the state of the art on the subject, reflecting on the aspects necessary to advance the subject in the Brazilian sphere.